Sustainable Catalytic Synthesis of Diethyl Carbonate. Issue 3 (4th December 2020) - Putro, Wahyu S.; Ikeda, Akira; Shigeyasu, Shinji; Hamura, Satoshi; Matsumoto, Seiji; Lee, Vladimir Ya.; Choi, Jun‐Chul; Fukaya, Norihisa
Abstract: New sustainable approaches should be developed to overcome equilibrium limitation of dialkyl carbonate synthesis from CO2 and alcohols. Using tetraethyl orthosilicate (TEOS) and CO2 with Zr catalysts, we report the first example of sustainable catalytic synthesis of diethyl carbonate (DEC). The disiloxane byproduct can be reverted to TEOS. Under the same conditions, DEC can be synthesized using a wide range of alkoxysilane substrates by investigating the effects of the number of ethoxy substituent in alkoxysilane substrates, alkyl chain, and unsaturated moiety on the fundamental property of this reaction. Mechanistic insights obtained by kinetic studies, labeling experiments, and spectroscopic investigations reveal that DEC is generated via nucleophilic ethoxylation of a CO2 ‐inserted Zr catalyst and catalyst regeneration by TEOS. The unprecedented transformation offers a new approach toward a cleaner route for DEC synthesis using recyclable alkoxysilane. Abstract : Regeneratable : The first example of a sustainable catalytic synthesis of diethyl carbonate (DEC) from CO2 and alkoxysilane substrate with Zr(OEt)4 catalysts is reported. That the disiloxane byproduct was regenerable offers a new promising direction for the development of waste‐free synthesis of DEC.